Treating food selectivity as resistance to change in children with autism spectrum disorder. Issue 4 (27th April 2020) - Crowley, Jaime G.; Peterson, Kathryn M.; Fisher, Wayne W.; Piazza, Cathleen C.
Abstract : Change‐resistant behavior, such as rigid and selective food consumption, is a core symptom of autism that can have significant negative consequences for the child (Flygare Wallén et al., 2018; Levy et al., 2019). In the current study, we used a matching‐law‐based intervention (Fisher et al., 2019) to treat the change‐resistant feeding behavior of 7 young children with autism. The feeder gave the participant a choice between a change‐resistant and an alternative food during free‐ and asymmetrical‐choice conditions. Alternative‐food consumption increased for 2 participants during asymmetrical choice when the feeder provided a preferred item for consuming the alternative food and no programmed consequence for consuming the change‐resistant food. Alternative‐food consumption increased for the other 5 participants after the feeder exposed at least 1 food to single choice in which the feeder guided the participant to put the bite of alternative food in his or her mouth if he or she did not do so within 8 s of presentation. Effects of the single‐choice contingencies maintained during reversals and generalized to other alternative foods the feeder did not expose to single choice. These results are important because participants consumed alternative foods even when their change‐resistant foods were present, which is similar to typical mealtime contexts in which children have choices among foods.